2014
DOI: 10.1007/s00217-014-2389-3
|View full text |Cite
|
Sign up to set email alerts
|

NIR and PLS discriminant analysis for predicting the processability of malt during lautering

Abstract: online trends. Both methods were compared to the expert opinion coinciding with 84 and 85 %, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Abnormal variations at the spectral level are also used to indicate potential outliers which would introduce error into the calibration model or that some erroneous error occurred during the scanning process which could be due to probe fouling or path length obstruction caused by aggregated cells. Principal component analysis is often used to classify sample scans in a qualitative or discriminant approach based on pattern recognition methods that are irrespective of reference data values . Grams AI was used to break each spectral scan down to its principle components in order to compare the relative weights (or scores) of each component from sample to sample.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal variations at the spectral level are also used to indicate potential outliers which would introduce error into the calibration model or that some erroneous error occurred during the scanning process which could be due to probe fouling or path length obstruction caused by aggregated cells. Principal component analysis is often used to classify sample scans in a qualitative or discriminant approach based on pattern recognition methods that are irrespective of reference data values . Grams AI was used to break each spectral scan down to its principle components in order to compare the relative weights (or scores) of each component from sample to sample.…”
Section: Resultsmentioning
confidence: 99%
“…Various calibrations have also been developed to measure parameters related to milled malt quality such as moisture, nitrogen, amino acids, fibre, starch and total β ‐glucans . In addition to monitoring quality parameters directly related to malt, research has shown that models can be developed to predict lautering performance based on NIR fingerprinting . Garden et al demonstrated that NIRS is a rapid and cost‐effective technique for measuring important hop constituents such as α ‐ and β ‐acids as well as the hop storage index.…”
Section: Introductionmentioning
confidence: 99%
“…The object of partial least squares is two data matrixes X(n × m x ) with Y(n × m y ). Partial least squares can solve the problems of collinearity [25] and insufficient samples [26] in traditional multivariate regression methods.…”
Section: Methodology 21 Partial Least Squares Methods (Pls)mentioning
confidence: 99%
“…The authors correlated the close relationship of the red and white varieties of C. paradise in the HCA dendrogram with their chemical similarities [54]. In a previous contribution, Krause et al (2015) utilized NIR spectroscopy combined with partial least squares regression for the quality analysis of brewing malt. Their study showed the capability of NIR spectroscopy as a fingerprinting technique for the classification of the processability of malt [56].…”
Section: Nir (Near-infrared Spectroscopy)mentioning
confidence: 99%